Retraction Note: Follicle stimulating hormone modulates ovarian stem cells through alternately spliced receptor variant FSH-R3 - Hiren Patel; Deepa Bhartiya; Seema Parte; Pranesh Gunjal; Snehal Yedurkar; Mithun Bhatt (BMC, 2023)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/1757-2215-6-52.